The relationship between rowing ergometer power and jumping characteristics - Bootes, M. (Journal of Australian Strength and Conditioning, 2017)
Ergometer training forms a substantial portion of elite rowing training and ergometer testing is an important part of the athlete selection process. Rowing is a strength endurance sport with high aerobic demands, maximal anaerobic power on rowing ergometers has been shown to be a good predictor of 2000m ergometer performance. The Seven Stroke Test (SST) test of maximal anaerobic power has also been used as a measure of functional rowing strength and force production. The aim of this study was to compare measures from the SST to non-specific force and power characteristics collected using force plate technology.